An unprecedented displacement of root piece in the infratemporal fossa: a case report. (7th January 2021) - Setiya, Sneha; Waknis, Pushkar P; Jain, Kunal M; Shah, Sonal
ABSTRACT: There are various reports of displaced maxillary third molar in the infratemporal fossa (IFT) in the literature. However there are no reported cases of a displaced root piece in the IFT. Here we have described a case of an accidental displacement of root piece of maxillary third molar into the IFT by a resident due to lack of surgical judgement and how this case was investigated and managed by our surgical team. There is no specific protocol for management of such complication in literature. The aim of this article is to identify the errors which lead to displacement of tooth in IFT and to establish a stepwise protocol to manage the same. We have highlighted a few basic steps for young practitioners to avoid such complications and also to manage them if at all they do occur.